The algorithm to directly generate tool phath and tool orientation with radiused end milling cutter when machining sculptured surfaces with five- axis machine tool - Nguyen, Hồng Thái; Le, Hiếu Giang; Nguyen, Văn Hưng (Journal of Technical Education Science, 2014)
In the process of finishing machining CNC, tool paths lead tool position points to sweep over the machined surfaces based on a determined rule. However, with five-axis machine tool, besides the positional location of cutting tool, we have to locate its orientation for each cutting point. Furthermore, in finishing machining sculptured surfaces, we usually use some milling cutters such as radiused-end mill, with each type of these tools, the geometric parameters, cutting characteristics and tool paths are different. In this article, with the input parameters: form of tool path parallel, geometric parameters of cutting tool, cross feed and cutting velocity, the authors proposes the algorithm to directly generate tool path and tool orientation with radiused -end milling cutter when machining sculptured surfaces with five-axis machine tool. The algorithm is programmed and simulated by MATLAB with some surfaces prametric S(u,v).